Mechanisms of action and therapeutic applications of GLP-1 and dual GIP/GLP-1 receptor agonists - Liu, Qiyuan Keith (Frontiers in Endocrinology, 2024)
Glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) are two incretins that bind to their respective receptors and activate the downstream signaling in a variety of tissues and organs. Both GIP and GLP-1 play a role in regulating food intake by stimulating neurons in the brain's satiety center. They also stimulate insulin secretion in pancreatic b-cells, but their effects on the glucagon production in pancreatic a-cells differ, with GIP have a glucagonotropic effect during hypoglycemia and GLP-1 exhibiting glucagonostatic effect during hyperglycemia. Additionally, GIP directly stimulates lipogenesis, while GLP-1 indirectly promotes lipolysis, collectively maintaining healthy adipocytes, reducing the ectopic fat distribution, increasing production and secretion of adiponectin from adipocytes. Together, these two incretins contribute to metabolic homeostasis, preventing both hyperglycemia and hypoglycemia, mitigating dyslipidemia, and reducing the risk of cardiovascular diseases in individuals with type 2 diabetes and obesity. Several GLP-1 and dual GIP/GLP-1 receptor agonists have been developed to harness these pharmacological effects in the treatment of type 2 diabetes with some demonstrating robust effectiveness in weight management and prevention of cardiovascular diseases. Elucidating the underlying cellular and molecular mechanisms could potentially usher the development of new generations of incretin analogues with enhanced efficacy and fewer adverse effects. The treatment guidelines are evolving based on clinical trial outcomes, shaping the management of the metabolic and cardiovascular diseases. Number of words: 11,580 Number of figures: 2 Number of tables: 2 Number of supplemental tables: 1 10 µg twice daily injection Yes 1 (2005) No No No No Exenatide ER (Bydureonâ; Amylin and Eli Lilly) 2 mg once weekly injection Yes (2012) No No No No Lixisenatide 2 (Adlyxinâ; Sanofi) 20 µg once daily injection Yes (2016) No No No No Albiglutide (Tanzeumâ; GlaxoSmithKline) 3 50 mg once weekly injection Yes (2014) No No No No Dulaglutide (TrulicityÒ; Eli Lilly) 4.5 mg once weekly injection